Effectiveness of Interventions Aimed at Improving Women's Employability and Quality of Work A Critical Review - Todd, Petra E. (The World Bank, 2012)
This paper examines the effectiveness of a variety of policy interventions that have been tried in developing and transition economies with the goal of improving women's employability and quality of work. The programs include active labor market programs, education and training programs, programs that facilitate work (such as childcare subsidies, parental leave programs and land titling programs), microfinance programs, entrepreneurship and leadership programs, and conditional cash transfer programs. Some of these policy interventions were undertaken to increase employment, some to increase female employment, and some for other reasons. All of these programs have been subjected to impact evaluations of different kinds and some also to rigorous cost-benefit analyses. Many were found to be effective in increasing women's quantity of work as measured by increased rates of labor market participation and number of hours worked. In some cases, the programs also increased women's quality of work, for example, by increasing the capacity for women to work in the formal rather than the informal sector where wages are higher and where women are more likely to have access to health, retirement, and other benefits